2006
DOI: 10.4319/lo.2006.51.4.1935
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency internal waves in the littoral zone of a large lake

Abstract: Observations in the littoral zone of a large lake (Lake Constance) revealed strong and periodic fluctuations of temperature and current velocity on timescales between 10 and 15 min associated with high‐frequency internal waves. The peak in the spectral energy of the current velocity fluctuations associated with high‐frequency internal waves follows the seasonal dynamics of stratification, described by the stability frequency N. A comparison between the nearshore current velocity measurements in the littoral zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…3a by the temperatures measured at 8 m and 4 m depth, is mainly characterized by a strong wind event on September 18, 2005 with wind speeds of up to 12 m s -1 . Before this wind event, both thermistors were within the seasonal thermocline and showed strong temperature fluctuations of up to 10°C on time scales of minutes to hours, which were caused by internal waves (Lorke et al, 2006). Wind-induced mixing resulted in a deepening of the surface mixed layer, such that the thermocline was below the depth of measurement.…”
Section: Resultsmentioning
confidence: 99%
“…3a by the temperatures measured at 8 m and 4 m depth, is mainly characterized by a strong wind event on September 18, 2005 with wind speeds of up to 12 m s -1 . Before this wind event, both thermistors were within the seasonal thermocline and showed strong temperature fluctuations of up to 10°C on time scales of minutes to hours, which were caused by internal waves (Lorke et al, 2006). Wind-induced mixing resulted in a deepening of the surface mixed layer, such that the thermocline was below the depth of measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Field studies in stratified medium or large lakes have identified important sources of turbulence in the density interface attributed to shear instabilities (Kelvin-Helmholtz-type billows) riding over the slope of IKWs (Lorke 2007;Preusse et al 2010). Furthermore, density inversion and interfacial breakings at the trough of a solitary wave train of large amplitudes have also been associated with the nonlinear degeneration of basin-scale IKWs (Preusse et al 2010(Preusse et al , 2012a.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…(a) t/T k = 0, (b) t/T k = 0.128, (c) t/T k = 0.25, (d) t/T k = 0.5, (e) t/T k = 0.75, (f ) t/T k = 1.0, (g) t/T k = 1.5, (h) t/T k = 1.75, (i) t/T k = 2.0, (j) t/T k = 2.25, (k) t/T k = 2.75, (l) t/T k = 3.0.The first three regimes have been analysed in previous numerical(de la Fuente et al 2008;Sakai & Redekopp 2010) and experimental studies(Wake, Ivey & Imberger 2005;Ulloa et al 2014), whereas the TR on IKWs has been observed only in field data(Lorke 2007;Preusse et al 2010) and to date in numerical experiments.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The primary result of this work that the bloom evolution into the center of the lake was controlled by physical processes and could be equally derived from normalized (uncalibrated) images because the relative concentrations returned from within an image are generally consistent. The seasonal evolution of wind and internal wave fields has been documented in many lakes (Lorke et al 2006;Mortimer 2006;Vidal et al 2007), and so the processes leading to bloom evolution are potentially similar in many systems. Future work will focus on the role of algal species in determining spatial patterns, and, in particular, the way in which the vertical migration capability of some species affects spatial variability (Hunter et al 2008).…”
Section: Discussionmentioning
confidence: 99%